2007
DOI: 10.1002/smll.200600481
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Properties of Silver‐Doped Titania

Abstract: Silver has been known to exhibit strong cytotoxicity towards a broad range of micro-organisms. Silver composites with a tailored slow silver-release rate are currently being investigated for various applications. [1] Silver has an oligodynamic effect, that is, silver ions are capable of causing a bacteriostatic (growth inhibition) or even a bactericidal (antibacterial) impact. Nanometer-sized inorganic particles and composites display unique physical and chemical properties and represent a unique class of mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
149
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(157 citation statements)
references
References 10 publications
7
149
0
1
Order By: Relevance
“…The deconstructed peak at 458.1 eV matches well with the presence of Ti 3+ , which can arise from the incorporation of silver on the matrix of TiO 2 [32] . 10 The effect of reactant concentration on the structures of TiO 2 /Ag composites was investigated. When the molar composition of Ti/Ag was 100 or 75, all the diffraction peaks matched well with the anatase TiO 2 (JCPDS standard card No.…”
Section: Synthesis and Characterization Of Tiomentioning
confidence: 99%
See 1 more Smart Citation
“…The deconstructed peak at 458.1 eV matches well with the presence of Ti 3+ , which can arise from the incorporation of silver on the matrix of TiO 2 [32] . 10 The effect of reactant concentration on the structures of TiO 2 /Ag composites was investigated. When the molar composition of Ti/Ag was 100 or 75, all the diffraction peaks matched well with the anatase TiO 2 (JCPDS standard card No.…”
Section: Synthesis and Characterization Of Tiomentioning
confidence: 99%
“…Cu [8] , Zn [9] , Ag [10] and Fe [11] ) and TiO 2 /non-metals composites [12][13][14] , so as to efficiently extend their utility as biomedical materials. Among these composites, TiO 2 /Ag composites are more potent antibacterial agents due to the fact that Ag nanoparticles (Ag NPs) deposited in TiO 2 matrix act as a conductor and charge separators for blocking electron-hole recombination, resulting in maximizing the production of ROS [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…Organic frameworks [6,7] and metal oxide supports [8][9][10] have frequently been used to maintain the dispersion of such noble metal nanoparticles. Due to their low price and ability to be prepared on a large scale, and since they are beneficial or, at worst, inert in processes catalyzed by noble metals, inorganic supports are preferred.…”
mentioning
confidence: 99%
“…(Morones et al, 2005). Moreover, we observed that the increase in the inhibition zone was more distinctive for S. aureus compared to E. coli as the Ag-NP size get smaller and this could be attributed to the cellular wall content differences between Gram-positive and Gram-negative bacteria as discussed by Thiel et al (2007).…”
Section: Resultsmentioning
confidence: 81%